Social Well-being and Related Factors in Workers Supporting Individuals with Developmental and Behavioral Disorders - Amani Obaidallah Ali Abuzahera (Journal of Educational and Human Sciences, 2022)
Social well-being is a complex concept that entails social contacts, the quality of the social contacts that a person has, and the level of interaction of the person within a social context. It is indeed the cornerstone of a person's general well-being, including the person's emotions and even bodily condition. Such social well-being is essential for care workers who tend to individuals with developmental and behavioural disorders. These workers are at a higher risk of experiencing job-related stressors, including high emotional demands, difficult behaviours and stigma that makes them lack good social relationships. Moreover, the kind of work they do requires a high level of interpersonal relationships that may build up or erode the staff member's social well-being depending on the prevailing supportive systems. The current paper aims to identify key determinants of social functioning that relate to care workers; these are work context, emotional workload, care support, organisational commitment, job performance, and training (Lopez et al., 2021). A clear appreciation of these aspects can enable the design of relevant intercessions that would facilitate the emotional and social functioning of care workers while at the same time supporting the quality of care afforded to people with developmental and behavioural issues.